Disorder, Coordination and Regional Differences of Core Elements in China’s Urbanization - Yi Han, Juanfeng Zhang, Hexin Lyu (Forest Chemicals Review, 1970)
China’s urbanization is considered significant measures in implementing the modernization and internationalization. The imbalance of three core elements, namely, population urbanization, land urbanization, and public goods supply, in time and space is a main negative aspect associated with urbanization. Therefore, coordinating the relationship among public goods, land, and population is the first priority. An empirical analysis was made to explore the relationship among the three core elements. Urbanization evaluation index systems for three core elements were set up, and the urbanization level and coordination index of 11 cities in Zhejiang Province were accomplished with coordination degree model. After analyzing the coordination degrees of the three core elements in urbanization in 11 cities in Zhejiang Province, we have accomplished two important solutions. First, we can scale up the supply of construction land to promote the coordination degrees of the three core elements in cities with overpopulation, traffic congestion, and overpriced housing and land problems caused by lagging development in land. Second, we can slow down the pace of land development, scale down the public goods supply, loosen the control on population inflow, and try to attract talents in all trades to boost the coordination degree of the three core elements in cities with great land development and timely public goods supply. When population urbanization rate reaches approximately 60%, China’s traditional urbanization model should be rethought and changed to improve the quality of urbanization. First, governments should relax the regulation on core elements, such as land bank system and household registration system for population. Local governments in China are controlling land resource allocation and public goods supply, which is a great hinder to rapid urbanization and destroys the development of the three core elements. In a word, if we want to see an ideal urbanization process, then local governments should guarantee a sound environment of land and labor markets and optimize the distribution of public goods supply in time and space.